Analysis of Students' Science Literacy Skills at SMAN 4 Makassar - Chaela Amelya Putri; Usman Usman; Trisno Setiawan (Department of Physics Education, Universitas Mataram, 2026)
This study aimed to assess the scientific literacy levels of Grade X students at SMAN 4 Makassar. The study population consisted of all 311 Grade X students enrolled at the school. Data were collected using a scientific literacy test developed based on the Programme for International Student Assessment (PISA) framework, comprising essay questions designed to measure three scientific literacy competencies within the topic of measurement. The results showed that the students' overall scientific literacy level was categorized as moderate, with a mean score of 61.59. Performance was evaluated across three scientific literacy competencies: identifying scientific issues, explaining scientific phenomena, and using scientific evidence. Among these, identifying scientific issues achieved the highest mean score (67.91, SD = 23.33), followed by explaining scientific phenomena (61.84, SD = 26.18). The lowest performance was observed in using scientific evidence, with a mean score of 42.31 (SD = 30.31). These findings indicate that while students demonstrated a moderate level of scientific literacy overall, their ability to use scientific evidence requires further improvement.